Contraception Recommendations With Analytical Hierarchy Process (AHP) and Weighted Product Methods (WP) - Audi Bayu Yuliawan; Nur Hayatin; Yufis Azhar (Jurnal Perempuan dan Anak, 2021)
Planning Program (KB) as one way to reduce the high rate of pregnancy. Contraceptives used in family planning programs have various types. In addition to the presence of contraception for women, contraception is also available for men. It's just that the problem at this time, lack of knowledge will choose contraception in accordance with health conditions. The limited time, place and expertise of experts to always provide information is one of the obstacles to getting complete information. Decision Support System is a knowledge-based computer information system that is used to support decision making in a problem. This system will later use the Analytical Hierarchy Process method, this method is a method that makes decision makers to get priority scale or consideration of experience, views, intuition and original data. Not only that this system will also use the Weighted Product (WP) method to maximize the performance of AHP in ranking the final results. This application is made using the Android programming language with Android Studio as the platform. In this application will later display recommendations for selecting contraceptives that are suitable for a patient.